White Matter Integrity Involvement in the Preclinical Stage of Familial Creutzfeldt–Jakob Disease: A Diffusion Tensor Imaging Study - Jing, Donglai; Chen, Yaojing; Xie, Kexin; Cui, Yue; Cui, Chunlei; Liu, Li; Lu, Hui; Ye, Jing; Gao, Ran; Wang, Lin; Liang, Zhigang; Zhang, Zhanjun; et al. (Frontiers in Aging Neuroscience, 2021)
Objective: To explore patterns of white matter (WM) alteration in preclinical stage familial Creutzfeldt-Jakob disease (fCJD) using diffusion tensor imaging (DTI). Methods: Seven asymptomatic carriers of the PRNP G114V mutation and six non-carriers were recruited from the same fCJD kindred and follow-up obtained from all asymptomatic carriers and two non-carriers 2 years later. Overlapping WM patterns were also explored in asymptomatic carriers and symptomatic CJD patients. All participants underwent clinical and neuropsychological assessments and DTI at baseline and follow-up. DTI data were subjected to whole-brain voxel-wise analysis of fractional anisotropy (FA) and mean diffusivity (MD) in WM using tract-based spatial statistics (TBSS). Three comparisons were conducted: baseline carriers against non-carriers (baseline analysis), changes after 2 years in carriers (follow-up analysis), and differences between patients with symptomatic CJD and healthy controls (CJD patient analysis). Results: Neither carriers nor non-carriers developed any neurological symptoms during 2 years of follow-up. Baseline analysis showed no differences between the carrier and non-carrier groups in MD and FA. Follow-up analysis showed significantly increased MD in multiple WM tracts, among which increased MD in the bilateral superior longitudinal fasciculus, bilateral anterior thalamic radiation, bilateral cingulate gyrus, and left uncinate fasciculus overlapped the patterns observed in patients with symptomatic CJD. Conclusion: Changes in integrity within multiple WM tracts can be detected during the preclinical stage of fCJD.